The disappearing God gap? religion in the 2008 presidential election - Smidt, Corwin E. 1946- (Oxford New York Oxford University Press, 2010)
"After the reelection of George W. Bush in 2004, the "God Gap" became a hotly debated political issue. Religious voters were seen as the key to Bush's victory, and Democrats began scrambling to reach out to them. Four years later, however, with the economy in a tailspin on election day, religion barely seemed to register on people's radar screens. In this book, a team of well-regarded scholars digs deeper to examine the role religion played in the 2008 campaign. They take a long view, placing the election in historical context and looking at the campaign as a whole, from the primaries through all the way through election day. At the heart of their analysis is data gleaned from a national survey conducted by the authors, in which voters were interviewed in the spring of 2008 and then re-interviewed after the election."--BOOK JACKET
Includes bibliographical references (p. [248]-271) and index. - Description based on print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion And Politics -- History -- 21st century -- United States; Presidents -- Election -- 2008 -- United States; Presidents -- United States -- Election -- 2008; Religion And Politics -- United States -- History -- 21st century; Religion And Politics; Präsidentenwahl; Wahlkampf; Religion; POLITICAL SCIENCE ; Political Process ; General; POLITICAL SCIENCE ; Political Process ; Elections; Presidents ; Election; History; United States -- Religion -- 1960- -- United States; United States -- Religion -- 1960-; Usa; United States; Electronic books -- History